AB1042 Pathologic musculoskeletal ultrasound findings in patients with chronic kidney disease on dialysis- a pilot controlled study. (12th June 2018) - Decianu, R.D.; Bojinca, M.; Capusa, C.A.; Zugravu, A.; Bojinca, V.C.
Abstract : Background: There are numerous studies about the musculoskeletal abnormities associated with dialysis, but most of them target osteoporosis and the bone metabolism. While this is, in fact, of great importance, we consider that the abarticular anomalies should also be taken into account. Because of the pain they cause and the quality of life impairment in patients already affected in this domain, suffering from depression or at its' edge. Objectives: We aimed to detect the dialysis associated soft tissue abnormalities, using musculoskeletal ultrasound(MSUS) scanning of patients diagnosed with late-stage chronic kidney disease(CKD) on dialysis. In order to achieve this, we compared the data obtained from this group, to a control group of pre-dialysis late-stage CKD. Methods: Over the last 8 months, we ran a prospective study including 102 patients. The study group included 52 patients with stage G5D (GFR <15 ml/min/1.73 m 2, on dialysis – hemodialysis (HD)/peritoneal dialysis (PD)), while the control group included 50 patients with stage G5 (GFR <15 ml/min/1.73 m 2, pre-dialysis). Each patient had 68 joints scanned with a Samsung HM70A machine, by the same ultrasonographist, in order to avoid the inter-observer variability. Also, each patient completed a visual analogue scale (VAS) for evaluating pain. Sex study group: M: 30 (57.69%) F: 22 (42.3%) Sex control group: M: 28 (56%) F: 22 (44%) Age (years) study group: 62, 52 30 – 82 Age (years) control group:64, 1 (33–84) HD/PD study group: HD: 46 (88.46%) DP: 6 (11.53%) Time on dialysis (years) study group: 6, 41 (0, 5–22) Results: The findings included median nerve entrapment (71.1% – study group, 18% – control group), tendon calcifications (61.5% – study group, 38% – control group), degenerative abnormalities (57.6% – study group, 50% – control group), synovitis (32.6% – study group, 22% – control group) and tenosynovitis (13.4% – study group, 8% – control group). There were no particular abnormalities found only in the study group, but the percentages of the common findings were significantly higher. The VAS results were split in three groups: low, moderate and high. Among the patients on dialysis, 46.1% declared a low VAS, 36.5% moderate and 17.3% a high VAS, while in the control group the distribution according to VAS was 46% in the low lot, 34% in the moderate and 20% in the high lot. Conclusions: We detected soft tissue abnormalities in an important percentage of patients on dialysis, but the results were disproportionate to the algo-functional symptoms. We found a higher percentage of low VAS then we were expecting. Considering the results, we plan to continue our study, aiming to create a rehabilitation programme adapted to the needs of the dialysed patient. References: [1] Gheita TA, Sayed S, Al-ghitany A, et al. Musculoskeletal Manifestations in Renal Hemodialysis Patiens. Ann Rheum Dis2016; 75(2):1260. [2] Yamazaki T, Kawahara N, Arai K, et al. Utility of Ultrasonography of the Median Nerve With a High-Frequency Probe for the Diagnosiis of Dialysis-Related Carpal Tunnel Syndrome, Ther Apher Dial2016; 20(5):483–491. Disclosure of Interest: None declared